A systematic review of development on motion-based games on upper extremities function for self-care ability among children with autism spectrum disorder - Ziming, Li; Hasley, Saiful; Romli, Muhammad Hibatullah; Azmeer, Raja Ahmad; Sulaiman, Puteri Suhaiza; Yingqiao, Xia; Chu, Qingqing; Wang, Beli (Asian Scholars Network, 2023)
In reaction to the pressing issue surrounding the self-care capacities of children with autism spectrum disorder, this paper reviews the existing empirical studies proving the usefulness of motion-based games therapy for children with autism spectrum disorder. This study is a systematic review of published studies. The databases Academic Search Complete, MEDLINE Complete，CINAHL, Scopus, and Eric were searched, revealing studies that were eligible for review. A total of 20 cross-sectional studies, all of which had relatively small samples, were included in the final analysis. Five included studies were from China, and six were from the USA. Most of the 20 studies employed experimental methodologies to investigate intervention moderation in a specific direction for children with autism. Fourteen employed qualitative research to examine the intervention and had fewer than or equal to 20 participants. The number of subjects in four studies topped 100,mostly in the form of quantitative research. The other four papers used a mixed-methods approach. This review demonstrates that interventions (interactive games such as somatosensory games, particularly for hand function training) can significantly enhance autistic children's self-care abilities. However, it is vital to do in-depth research on these therapy tools, given the basic state and growth of children with ASD.